Effects of different regimens of iron prophylaxis on maternal iron status and pregnancy outcome: a randomized control trial. (3rd August 2017) - Parisi, Francesca; Berti, Cristiana; Mandò, Chiara; Martinelli, Anna; Mazzali, Cristina; Cetin, Irene
Abstract: Purpose : Iron supplementation is associated with side effects and overload risk. We compared different regimens of iron supplementation on maternal hematological status and pregnancy outcome in a cohort of healthy pregnant women. Materials and methods : Eighty non-anemic women with a normal singleton pregnancy were recruited at 11–13 weeks and randomized into controls (C; n = 20) and groups supplemented with ferrous iron 30 mg (FI; n = 20), liposomal iron 14 mg (Sideral® Pharmanutra, Pisa PI, Italy) (LI14; n = 20) and liposomal iron 28 mg/daily (LI28; n = 20) up to 6 weeks post-partum. Longitudinal maternal blood samples for iron markers were collected. Data on birth outcome were recorded. The treatment effect was evaluated using a mixed-effect regression model. Results : Both LI28 and LI14 groups showed significantly higher hemoglobin and ferritin concentrations compared with controls. Birth weight showed a trend to increase with supplementation, resulting in higher birth weight in the LI28 group compared with controls (3499 ± 464.1 g and 3092 ± 469.5 g, respectively, p < 0.01). Conclusions: Our data show the effectiveness of 28 mg and 14 mg LI on maternal anemia prevention, as previously reported with FI 40 mg. LI has similar effects of higher doses of ferrous iron on maternal hematological parameters, thus allowing to reduce iron doses and side effects.